Phytotoxicity assessment of nano-ZnO on goundnut (Arachis hypogaea) seed germination in MS medium - Dastjerdi, Ehsan Borzouyan; Ismail Sahid,; Khairiah Jusoh, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Due to the increasing production and use of nanoparticles in various sectors such as electronic industries and healthcare, concerns about the unknown effects caused by the presence of these materials in the natural environment and agricultural systems were on the rise. Because of the growing trend of ZnO nanoparticles (nZnO) which is one of the most widely used nanoparticles being released into the environment, it has attracted the attention for more studies to be done on the effects of this nanoparticle on organisms. This study was carried out to investigate the phytotoxicity effect of nZnO on groundnut seedlings in Murashige and Skoog (MS) medium. The experimental treatments of this study include eight concentrations of nZnO (10, 30, 50, 100, 200, 400, 1000 & 2000 mg.L-1) added to MS medium and MS medium without nanoparticles have been used as control treatment. For the first 6 days after sowing, germination percent and germination rate index were calculated by counting the germinated seeds every day. Groundnut seedlings were incubated for 3 weeks in optimum condition and after that, seedling characteristics such as length, wet and dry weight of radicle and plumule were measured. The water content of radicle and plumule were also calculated. The results of this study showed that radicle and plumule length of groundnut seedlings were affected by nZnO exposure, in a way that length of radicles in 50 mg.L-1 nZnO and higher concentrations was significantly lower than that of control treatment and the shortest plumule length was observed in 2000 mg.L-1 nZnO concentration treatment. Both the radicle and plumule wet weight were also decreased as the nanoparticle concentration was increased. However, despite the decreasing in radicle and plumule dry weight with increasing in nZnO concentration, this increase was not significant. However radicle dry weight in 10 mg.L-1 nZnO was significantly higher than nZnO treatments with 200 mg.L-1 concentration and higher concentrations. Moreover, observations of this study did not show any significant difference between the water content of nZnO concentration treatments and control treatment.